2021
DOI: 10.3389/fendo.2021.740902
|View full text |Cite
|
Sign up to set email alerts
|

Sex Dimorphic Associations of Gestational Diabetes Mellitus With Cord Plasma Fatty Acid Binding Protein 4 and Estradiol

Abstract: Fatty acid binding protein 4 (FABP4) has been associated with insulin resistance. Gestational diabetes mellitus (GDM) impairs fetal insulin sensitivity. Female newborns are more insulin resistant than male newborns. We sought to evaluate the association between GDM and cord blood FABP4, and explore potential sex dimorphic associations and the roles of sex hormones. This was a nested case-control study in the Shanghai Birth Cohort, including 153 pairs of newborns in GDM vs. euglycemic pregnancies matched by inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Interestingly, the current study did not show statistically significant differences between the concentration of tested hormones in the umbilical cord blood in the group of children from healthy mothers, and from mothers with GDM (data not shown). This is consistent with previous literature data [21], but despite this, interesting interactions were observed that varied depending on the study group. The first interesting observation made during the presented study was the data that did not show greater growth in offspring from women with GDM, which is very often described in the literature.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, the current study did not show statistically significant differences between the concentration of tested hormones in the umbilical cord blood in the group of children from healthy mothers, and from mothers with GDM (data not shown). This is consistent with previous literature data [21], but despite this, interesting interactions were observed that varied depending on the study group. The first interesting observation made during the presented study was the data that did not show greater growth in offspring from women with GDM, which is very often described in the literature.…”
Section: Discussionsupporting
confidence: 93%
“…In line with these findings, Ron et al, also reported higher AFABP levels in fetal circulation when compared with AFABP levels in maternal serum and an inverse correlation between cord AFABP and blood glucose of neonates, with a ten-fold increase of umbilical AFABP levels in infants with hypoglycemia [95]. A nested case-control study described a positive correlation between GDM and cord blood AFABP in male offspring, but this correlation was not true for female neonates [96].…”
Section: Cord Blood Afabpmentioning
confidence: 78%
“…This could be explained via an overstimulation of ERα by E2, which could provoke IR in the liver and depletion of β-cells, possibly contributing to diabetic phenotypes [ 28 ]. Moreover, GDM was associated with elevated E2 cord plasma concentrations in male newborns [ 29 ].…”
Section: Introductionmentioning
confidence: 99%